Chronic Traumatic Encephalopathy in a Routine Neuropathology Service in Australia. Issue 10 (10th August 2022) - Suter, Catherine M; Affleck, Andrew J; Lee, Maggie; Davies, Danielle; Burns, Arran L; Sy, Joanne; I'Ons, Bernard; Buckland, Michael E
Abstract: Chronic traumatic encephalopathy (CTE) is a neuropathological diagnosis defined by a unique pattern of hyperphosphorylated tau (p-tau) accumulation that begins in neocortical regions of the brain. It is associated with a range of neuropsychological symptoms, but a definitive diagnosis can only be made by postmortem brain examination. In 2018, we instituted CTE screening for all autopsy brains as part of our routine departmental protocol by performing p-tau immunohistochemistry on a restricted set of 3 neocortical blocks (frontal, temporal, and parietal). This strategy allowed us to identify 4 cases of low-stage CTE from 180 consecutive autopsies. Two of the 4 cases had a documented history of brain injury; for the remaining 2 cases, there was a long history of treatment-resistant tonic/clonic epilepsy suggesting that undocumented brain injuries may have occurred. Our experience indicates that 3-block CTE screening is useful in identifying CTE in routine practice. The results of this study further support the association between prior head injuries and CTE and demonstrate that, albeit uncommon, CTE does occur in the general population. Our findings suggest that p-tau screening should be routinely pursued in brain autopsy, particularly where there is a documented or likely history of traumatic brain injury.